Availability of betaine present in fine wheat bran in diets for growing pigs - Somensi, Marcelo Luiz (2019)
The objective of this paper was to investigate the availability of betaine present in fine wheat bran (FWB) in diets for growing pigs. We used thirty crossbred intact males, housed individually in metabolic cages and distributed in a randomized block design, with five treatments and six replicates. Blocks consisted of two periods of 15 days. Average initial body weights were 32.00±1.30 and 44.90±1.32 kg, in the first and second periods, respectively. Treatments were modified only at the level of methionine plus cysteine (Met+Cys) required and the Met+Cys sources, consisting of a negative control (NC), formulated with 80% of Met+Cys requirements, and four positive controls (PC): PCMet - NC supplemented with 1.2 g kg−1 of DL-methionine; PCBet - NC supplemented with 0.9 g kg−1 of anhydrous betaine; PCFWB - diet formulated with FWB; and PCFWB+Met - PCFWB supplemented with 1.0 g kg−1 of DL-methionine. No differences were observed on performance-related variables or on the digestibility coefficient of dry matter. Conversely, the digestibility coefficient of crude energy was lower when pigs were fed FWB and could be associated to the higher fiber content of FWB feeds. Digestible energy of feeds was higher for FWB diets, while the metabolizable energy of FWB diets did not differ from PCMet and PCBet. Nitrogen intake and apparent absorption were lower when pigs were fed FWB, but nitrogen retention, protein utilization, and biological value of the feed protein were the same among PC treatments, indicating that nitrogen from diets was used by pigs with the same efficiency, and is supported by no differences in performance-related variables. The FWB composition showed 12 g of betaine kg−1, which is available to maintain nitrogen retention and performance.